2020
DOI: 10.1371/journal.pone.0235234
|View full text |Cite
|
Sign up to set email alerts
|

Determination of reference intervals for common chemistry and immunoassay tests for Kenyan adults based on an internationally harmonized protocol and up-to-date statistical methods

Abstract: Background Due to a lack of reliable reference intervals (RIs) for Kenya, we set out to determine RIs for 40 common chemistry and immunoassay tests as part of the IFCC global RI project. Methods Apparently healthy adults aged 18-65 years were recruited according to a harmonized protocol and samples analyzed using Beckman-Coulter analyzers. Value assigned serum panels were measured to standardize chemistry results. The need for partitioning reference values by sex and age was based on between-subgroup differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 23 publications
(45 reference statements)
0
17
0
Order By: Relevance
“…Several studies have shown that the RIs established by the parametric method are narrower than those established by the nonparametric method. 22 , 29 Furthermore, different compositions and performances were found in the instruments, which led to various test results. The difference in the RIs for C3, compared with other studies, was more significant than that for C4; this phenomenon has occurred in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the RIs established by the parametric method are narrower than those established by the nonparametric method. 22 , 29 Furthermore, different compositions and performances were found in the instruments, which led to various test results. The difference in the RIs for C3, compared with other studies, was more significant than that for C4; this phenomenon has occurred in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…We use the critical value of SDR>0.3 to signify significant difference between sex-specific assay medians to warrant sex-specific RIs. As SDR is a measurement of different from the point of centrality, we also include a comparison metric, “Bias Ratio” (BR), which may more appropriately characterize difference between groups at the extremes of the distribution [ 30 ]. The BR calculation examines the dispersion for the RI at the extremes for male and female values compared to the extremes for the combined population divided by standard deviation (SD) comprising reference interval (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…In order to depict the practical magnitude of the statistical difference between male and female RIs, we calculate the standard deviation ratio (SDR) using a 1-way ANOVA approach to determine the within-group deviation from the overall median value [28][29][30]. We use the critical value of SDR>0.3 to signify significant difference between sex-specific assay medians to warrant sex-specific RIs.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…for the nomenclature, terminology, units and formats used, to ensure reproducibility of all the steps of the total laboratory testing procedure, possibly for international application[10,11]. This is an on-going global process, as laboratories in Europe[1217], Africa[1820], North America[21], Asia[2224] and Australia[25] aim to derive nation-specific RIs with multicentre studies.…”
Section: Introductionmentioning
confidence: 99%